2013
DOI: 10.1007/s10753-013-9671-6
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effects of Desflurane and Propofol Anesthesia on the Inflammatory Response and S100β Protein During Coronary Artery Bypass Grafting

Abstract: Cardiopulmonary bypass (CPB) contributes to the secretion of anti-inflammatory cytokines that mediate the inflammatory response observed during open heart surgery. In addition to many factors, type of anesthesia management affects immune response and central nervous system in cardiac surgery. The aim of this study was to assess the effect of propofol versus desflurane anesthesia on systemic immune modulation and central nervous system on patients undergoing coronary artery bypass grafting. Forty patients under… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
36
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 30 publications
0
36
2
Order By: Relevance
“…[17][18][19] All the articles had reported exclusion/inclusion criteria. [17][18][19][20][21][22][23][24][25][26][27][28][29] Of these, seven studies had used isoflurane versus TIVA, 17 19-21 23 24 27 four studies Open Access had used sevoflurane versus TIVA 18 22 25 26 and two studies had used desflurane versus TIVA 28 29 in patients.…”
Section: Results Characteristics Of the Included Studiesmentioning
confidence: 99%
“…[17][18][19] All the articles had reported exclusion/inclusion criteria. [17][18][19][20][21][22][23][24][25][26][27][28][29] Of these, seven studies had used isoflurane versus TIVA, 17 19-21 23 24 27 four studies Open Access had used sevoflurane versus TIVA 18 22 25 26 and two studies had used desflurane versus TIVA 28 29 in patients.…”
Section: Results Characteristics Of the Included Studiesmentioning
confidence: 99%
“…However, Tylman (Tylman et al, 2011) et al believed that these 2 anesthetic agents had similar impact on patients' immunological responses. Baki (Baki et al, 2013) et al randomly divided 40 patients with coronary artery diseases underwent selective operations into 2 groups and treated with propofol and desflurane respectively, and the results demonstrated that serum IL-6 and IL-8 levels in propofol group were evidently higher than those in desflurane group. Inhalation anesthesia of isoflurane or enflurance is commonly used in clinic, whose effect on organic cytokine expressions has become the research focus of abundant scholars (Kumakura et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Other drugs with expected immune modulatory effects have also been tested: the anesthetic propofol had a positive influence on the immune response after CPB [81]. Furthermore, it was found that S100β levels were lower in patients receiving propofol in contrast to patients under desflurane anesthesia [82].…”
Section: Pharmacological Methods For Brain Protectionmentioning
confidence: 99%